DAMPAK STRATEGI PROMOSI DENGAN MEDIA ONLINE TERHADAP PENYEDIA JASA HOSTING DENGAN STUDI KASUS PADA PASARHOSTING.COM - Aprianto Miduk Pandapotan Saragih (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Based on the description that has been stated, a study was conducted to analyze Pasarhosting.com''s online promotion using the Analytical Hierarchy Process (AHP) method entitled " Impact Of Promotional Strategies With Online Media On Hosting Service Providers With Case Study On Pasarhosting.Com". The analytic hierarchy process includes both qualitative and quantitative aspects of the human mind. The qualitative aspect is to define the problem and its hierarchy, and the quantitative aspect is to express judgments and preferences in a concise mannerthe essence of this research is to identify Pasarhosting.com''s online promotion strategy by prioritizing the advantages of its products, knowing the factors, actors, goals through hierarchical preparation and setting priorities, as well as the existence of alternatives for preparing company promotion strategies. For this reason, a promotion strategy was selected using the AHP analysis tool according to the hierarchy to assist the priority setting process, starting with determining the factors, actors, objectives and alternatives of Pasarhosting.com online promotion strategyThere are five (5) factors that make up Pasarhosting.com online promotion strategy, namely Competitors, Market Analysis, STP, Technology, Availability of Time and Human Resources. Competitors have the highest influence in determining Pasarhosting.com''s promotional mix The second priority is the Market Analysis factor The most influential actor at Pasarhosting.com is the CEO The most desired goal is to increase sales of Pasarhosting.com domains and hosting.The best alternative Pasarhosting.com online promotion strategy to implement is promotion through social media, followed by SEO, webverting, web experience and direct promotion via e-mail. Pasarhosting.com must give sufficient time to analyze the market that continues to grow, it is necessary to develop an online promotion strategy according to the rapid increase in technology.